2012
DOI: 10.1108/13552551211239500
|View full text |Cite
|
Sign up to set email alerts
|

Developing business school/SMEs collaboration: the role of trust

Abstract: PurposeTo investigate the initiation and development of effective business relationships, including knowledge transfer partnerships, with the primacy of trust as a key factor for collaborative development. Specifically, the aim was to explore Vangen and Huxham's (2003) notion of a “trust building loop” in the context of a Northern (UK) Business School and regional SMEs.Design/methodology/approachThe methodological approach employed was the “General Analytic Induction” for the interpretation of the data. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…Whilst the rationale case studies can be made on the basis that examining one single entity can result in gaining a deeper understanding of a phenomenon, published work on turnaround has been limited by a lack of comparative case study work. We see value in theorising about consistencies and differences across NGBs using a more analytical form of qualitative inquiry (Darabi & Clark, 2012;Dyer & Wilkins, 1991;Glaser, 1965).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst the rationale case studies can be made on the basis that examining one single entity can result in gaining a deeper understanding of a phenomenon, published work on turnaround has been limited by a lack of comparative case study work. We see value in theorising about consistencies and differences across NGBs using a more analytical form of qualitative inquiry (Darabi & Clark, 2012;Dyer & Wilkins, 1991;Glaser, 1965).…”
Section: Methodsmentioning
confidence: 99%
“…Trust is recognized as a necessary element of effective collaboration, which influences the managerial approach [69]. Moreover, it has been confirmed that trust enables effective team collaboration [70,71]. Therefore, we assumed that trust is an essential factor that binds team members together and thus facilitates team effectiveness.…”
mentioning
confidence: 95%
“…The importance of enterprises and entrepreneurship for future development is undeniable considering that SMEs generally account for approximately 95% of a country's economy (Shaw and Allen, 2006). Therefore, the long-term objective of business schools has increasingly been to become more involved in regional economic and social development through closer business and industry collaboration, such as management and leadership education programs (Darabi and Murray, 2012). This has resulted in the changing role of the higher education sector.…”
Section: Management Education and Needs Of Smementioning
confidence: 99%